A study of the temperature dependence of the infrared absorption cross-sections of 2, 2, 3, 3, 3-pentafluoropropanol in the range of 298–362 K. (January 2017) - Godin, Paul J.; Cabaj, Alex; Xu, Li-Hong; Le Bris, Karine; Strong, Kimberly
Abstract: Absorption cross-sections of 2, 2, 3, 3, 3-pentafluoropropanol (PFPO) were derived from Fourier transform infrared spectra recorded from 565 to 3400 cm −1 with a resolution of 0.1 cm −1 over a temperature range of 298–362 K. These results were compared to previously published theoretical density functional theory (DFT) calculations and experimental measurements made at room temperature. We find good agreement between our experimentally derived results, DFT calculations, and previously published data. The only temperature dependence observed was in the centroid shift of the 850–1500 cm −1 band and in the amplitude of some of the absorption peaks. However, this temperature dependence does not result in a significant trend in integrated band strength as a function of temperature. We calculate an average integrated band strength of (1.991±0.001)×10 −16  cm molecule −1 for PFPO over the spectral range studied. Radiative efficiencies (REs) and the global warming potential (GWP) for PFPO were also derived. We find an average RE of 0.2603 ± 0.0007 W m − 2 ppbv − 1 and a GWP100 of 19.8. The calculated radiative efficiencies show that no dependence on temperature and our findings are consistent with previous studies, increasing our confidence in the value of the GWP of PFPO. Abstract : Highlights: Cross-sections of 2, 2, 3, 3, 3-pentafluoropropanol (PFPO) were measured from 565–3400 cm −1 . Good agreement between new results, prior data, and density functional theory. Temperature dependence observed in centroid position of 850–1500 cm −1 band and height of peak absorption. No observed temperature dependence in the radiative efficiencies over the range of 298–362 K. Global warming potential agrees with previous data and increases our confidence in these numbers.